Shining lights and bad apples: The effect of goal-setting on group performance. Issue 3 (July 2014) - Curşeu, Petru L; Janssen, Steffie EA; Meeus, Marius TH
Management education programs increasingly use group work as a tool for developing teamwork knowledge and skills. A critical factor identified in prior research to influence group performance in student groups is goal-setting. We test in a sample of 37 groups the effect of group goal configurations and goal difficulty on group performance. We show that goal distance (as the distance between the lowest goal in the group and the rest of individual goals) has a positive impact on group performance. Moreover, we provide empirical evidence for an inverted U-shape association between goal difficulty and group performance. Therefore, our results question the linearity assumptions on the relation between goal difficulty and group performance and open new research directions in group goal-setting.